Variation of stiffness of two magnetically coupled beams for broadband energy harvesting - Xiao, Jincheng (2014)
Smart structural health monitoring through wireless sensors is gaining significant importance over the past few decades. Consequently, many researchers are trying to power such sensors by harvesting energy from ambient energy sources. Vibration energy, when compared to other energy sources such as solar and wind power, is more abundant and readily available. Hence vibration was adopted in this research as the energy source to generate electricity to power the sensors. The conventional way to acquire vibration energy was linear piezoelectric energy harvesting (PEH). However the limited frequency bandwidth limits its efficiency. To overcome this limitation, a new non-linear PEH configuration with two magnetically coupled cantilever beams positioned perpendicular to each other is proposed in this study. The non-linearity was introduced through the interaction of the tip magnets on the cantilever beams. The open circuit voltage outputs were first determined for both linear and non-linear PEH systems and compared to find the suitable material for the cantilever beams. The excitation level and the direction of magnetic poles of the tip magnets were changed to investigate the behavior of the non-linear PEH system. The distances between the tip magnets was changed to find the optimal configuration for this non-linear PEH system. The proposed configuration was investigated experimentally and the most efficient setup and material was arrived at, by the end of the study.